Synthesis, structural and electrical properties of granular BT-NZF nanocrystals in silicate glass - Pratthana Intawin (2018)
© 2017 In this work, glass-ceramics from the Ni0.8Zn0.2Fe2O4(NZF)-BaTiO3(BT)-Na2O-B2O3-SiO2system have been synthesized and characterized by the conventional melt quenching method. In order to change the prepared glass to glass-ceramic samples, a heat treatment technique was employed using temperatures ranging between 550 and 800 °C. Glass transition and crystallization temperatures were investigated by differential thermal analysis. The thermal data were used to determine the glass crystallization. Glass can undergo crystallization upon heat treatment when the amorphous component converts into crystalline material. The X-ray diffraction patterns showed the presence of the amorphous phase and the precipitation crystalline phase in the amorphous matrix. The morphology of the crystals was studied by scanning electron and transmission electron microscopes. Magnetic hysteresis loops were analyzed using a vibrating sample magnetometer with a maximum applied field of 10 kOe at room temperature. The dielectric properties were measured at various frequencies and temperatures using a precision LCZ meter. Finally, the ferroelectric hysteresis loops were measured using a Sawyer Tower circuit at room temperature. From the results it can be concluded that magnetization behavior was improved in BT-NZF-Silicate glass-ceramics with increasing heat treatment temperature. Crystallization of ferroelectric phase optimized ferroelectric and dielectric properties at the same time. Therefore this glass ceramic system can be a potential new material for combining ferroelectric and magnetic properties.